Maltreatment in childhood and perceived partner responsiveness in adult romantic relationships: a dyadic daily diary and longitudinal study - Vaillancourt-Morel, Marie-Pier (Child maltreatment, 2023)
This study examined the associations between childhood maltreatment (CM) and the mean-level of perceived partner responsiveness (PPR; the extent to which individuals feel cared for, understood, and validated by their partner) over 35 days, the day-to-day variability in PPR, and the initial levels and trajectories of PPR over 1 year in community couples. Both members of 228 couples completed a self-reported measure of CM and provided daily reports of PPR over 35 days and retrospective reports of PPR at three time points over 1 year. A person?s greater CM was related to a lower mean level of PPR over 35 days and to a lower initial level of their own PPR. A person?s sexual abuse, physical neglect, and emotional neglect had an effect over and above other forms of CM in these associations. A person?s greater CM was also related to higher day-to-day variability in their own and their partner?s PPR, and a person?s greater emotional neglect was associated with a sharper decrease over time in their own PPR. These findings provide a more fine-grained understanding of how CM may affect the perceptions of being cared about, accepted, and validated by a partner on a daily basis and over time.